2012
DOI: 10.1021/jp3093034
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insight Into the Hydrogen Bonding and Micro-Segregation of a Cryoprotectant Molecule

Abstract: Glycerol-water liquid mixtures are intriguing hydrogen-bonded systems and essential in many fields of chemistry, ranging from basic molecular research to widespread use in industrial and biomedical applications as cryoprotective solutions. Despite much research on these mixtures, the details of their microscopic structure are still not understood. One common notion is that glycerol acts to diminish the hydrogen bonding ability of water, a recurring hypothesis that remains untested by direct experimental approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
86
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 58 publications
6
86
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Neutron diffraction experiments have been used to study an aqueous solution of 30 mol% PG, containing 200 mM of 1,2-dipropionyl-sn-glycero-3-phosphocholine (C 3 -PC). The neutron diffraction experiments were performed on the SAN-DALS diffractometer at the ISIS neutron facility, UK.…”
Section: A Neutron Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Neutron diffraction experiments have been used to study an aqueous solution of 30 mol% PG, containing 200 mM of 1,2-dipropionyl-sn-glycero-3-phosphocholine (C 3 -PC). The neutron diffraction experiments were performed on the SAN-DALS diffractometer at the ISIS neutron facility, UK.…”
Section: A Neutron Diffractionmentioning
confidence: 99%
“…Empirical Potential Structure Refinement (EPSR) modeling 7 can be used to create a model which 'fits' the measured diffraction data and has been used for a variety of systems to gain a better understanding of the structure of molecules in solution. [11][12][13][14][19][20][21][22] EPSR is Monte Carlo-based simulation which begins with a set of established potentials and then refines these potentials iteratively until a good fit between the measured data and the model is achieved. The EPSR simulation box here contained 10 C 3 -PC lipids, 750 PG molecules (375 R-and 375 S-) and 1750 water molecules (Fig.…”
mentioning
confidence: 99%
“…al. used neutron scattering in combination with Reverse Monte Carlo (RMC) simulations to study the hydrogen-bonded structure in glycerol [59] as well as in glycerol-water mixtures [60][61][62][63]. They find that in neat glycerol each molecule forms on average 5.68 ± 1.51 hydrogen bonds, while for neat water the average number of hydrogen bonds per molecule is about 3.56±1.10.…”
Section: B Glycerol-water Mixturesmentioning
confidence: 99%
“…This method has been applied previously to study pure glycerol and glycerol-water mixtures at room temperature. [67][68][69][70][71] In the present study we examine the structure at low temperature for the first time and compare with the room temperature data. The SPC model was employed as the RP for water molecules.…”
Section: Empirical Potential Structural Refinement Analysismentioning
confidence: 99%
“…56,[65][66] In the last 4 years we have completed experimental, structural studies of pure glycerol and glycerol-water mixtures at 298 K using a combination of neutron diffraction and computational modeling. [67][68][69][70][71] Our studies have shown that at intermediate concentrations (between x g = 0.25 to 0.50) the mixture segregates on the nanometer length scale to form waterrich and glycerol-rich clusters. [70][71] This nano-segregation results in regions which exist as hydrogen bonded clusters which differ in size across the concentration range.…”
mentioning
confidence: 99%